Comparison of corporate governance, strategy, control and performance e valuation systems before and after privatization - Cuevas-Rodríguez, Gloria; Guerrero-Villegas, Jaime; Valle-Cabrera, Ramón (Revista Internacional de Organizaciones, 2016)
The aim of this paper is compare corporate governance and firm strategy before and after privatization. The design of control and performance evaluation systems in the pre and post-privatization periods is compared so that it can be understood in relation to the changes observed at a high corporate level (corporate governance and firm strategy). We carry out various case studies on five privatized Spanish companies. The results support several conclusions. First, the variables that are traditionally related to greater board independence in monitoring do not undergo variation after privatization. Second, the interests of the firms' new ownership have an impact on firm strategy after privatization. Finally, control and performance evaluation system designs clearly align with firm strategy after privatization.